The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1042/bsr20090128
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of non-cytosolic hexokinase activity in white skeletal muscle from goldfish (Carassius auratus L.) and the effect of cold acclimation

Abstract: HK (hexokinase) is an enzyme involved in the first step in the glucose metabolism pathway, converting glucose into G6P (glucose 6-phosphate). Owing to the importance of skeletal muscle for fish swimming and acclimation processes, we used goldfish (Carassius auratus L.) white muscle in order to investigate subcellular distribution and kinetics of HK. In this study, we report that HK activity is predominantly localized in the mitochondrial fraction [NC-HK (non-cytosolic HK)] in goldfish white muscle. Studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
2
3
0
Order By: Relevance
“…Figure 3 C shows that the HK activity of the fish increased gradually with increasing live transport time. This is similar to previous research results; the present study demonstrated that cold conditions induce an increasing trend in the HK activity of fish [ 54 , 55 , 56 ]. PK activity increased at the highest rate in the CK group, indicating that the stress response of the sea bass in this group was the strongest and that the rate of glycolysis was accelerated to resist the stress response.…”
Section: Resultssupporting
confidence: 93%
“…Figure 3 C shows that the HK activity of the fish increased gradually with increasing live transport time. This is similar to previous research results; the present study demonstrated that cold conditions induce an increasing trend in the HK activity of fish [ 54 , 55 , 56 ]. PK activity increased at the highest rate in the CK group, indicating that the stress response of the sea bass in this group was the strongest and that the rate of glycolysis was accelerated to resist the stress response.…”
Section: Resultssupporting
confidence: 93%
“…The hexokinase type 2 gene is involved in the glycolytic pathway and may play an important role in increasing glucose content [46]. Its expression was up-regulated in the cold acclimation group after 24 h at 0 °C, consistent with previous studies in goldfish (Carassius auratus L) [47]. Additionally, the decreased expression of UTP-glucose-1-phosphate uridylyltransferase and glycogenin-1 involved in glycogen synthesis may inhibit metabolic pathways related to synthesis of glucose and glycogen.…”
Section: Table 1 Number Of Differential Expression Mrna and Lncrna In...supporting
confidence: 88%
“…Using a protocol for cold acclimation described previously by our group (dos Santos et al, 2010), we measured the different mitochondrial respiratory states in white muscle mitochondria isolated from warm-acclimated and cold-acclimated goldfish (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Fish (20–30 g) were maintained at 25°C on a 12 hour:12 hour light/dark cycle and were generally used within 1–1.5 months of arrival. The acclimation was performed using a refrigeration unit (347 CDG-FANEM®, São Paulo, Brazil) as described previously (dos Santos et al, 2010). Fish were kept at least for three days in the lab before starting the experiment in order to minimize the potential stress caused by transportation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation